KAJIAN INTERAKSI OBAT ANTIHIPERTENSI PADA PASIEN HEMODIALISIS DI BANGSAL RAWAT INAP RSU PKU MUHAMMADIYAH YOGYAKARTA PERIODE TAHUN 2010 - Siti Rahmiati; Woro Supadmi (Pharmaciana, 2012)
Drug interactions are one of the Drug Related Problems (DRPs) that may affectpatient treatment outcomes. Hypertension occurs in approximately 10% to 81.5% ofhemodialysis patients. The purpose of this study was to determine the incidence ofantihypertensive drug interactions in hemodialysis patients in the inpatient wards PKUMuhammadiyah Hospital of Yogyakarta period in 2010. This study descriptive design.Data retrieved retrospectively. Data retrieval were done by taking all the data thatmeet the criteria of existing research on the medical records of hemodialysis patients inPKU Muhammadiyah Hospital of Yogyakarta who received antihypertensive withabove normal blood pressure (= 130/80 mmHg). Data were analyzed based on thedescriptive level of significance, onset, and severity. The results showed that there were54.79% (40 patients) of 73 hemodialysis patients potentially experienced druginteractions. Antihypertensive drugs most widely used in hemodialysis patients wereACEI, CCB, and diuretics. Incidence of antihypertensive drug interactions 27 cases(45.76% were most common at a significance level 3, 48 cases (81.36%) were onsetdelayed, and the severity minor of 44 cases (74.58%). The mechanism of interactionspharmacodynamic were 37 cases (62.71%) of the total 59 events that have druginteractions. Drugs often interactions were furosemide and captopril.